2022
DOI: 10.3390/brainsci12101391
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Changes in the Retina Correlate with MRI Markers in Patients with Early-Onset Dementia

Abstract: Recent reports suggest that results from imaging retinal microvascular changes with optical coherence tomography angiography (OCTA) in dementia patients reflect cerebral microcirculation changes that occur during dementia. Macula microvascular impairment has been shown in dementia patients compared to controls, but very little is known about its correlation with radiological visual rating scores associated with dementia. We aimed to explore the association between retinal microvasculature and radiological visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In 2018, O’Bryhim et al noted that Aβ-positive preclinical patients had a greater foveal avascular zone (FAZ) on their OCTA in comparison to healthy people [ 60 ]. Subsequent studies by Zhang in 2022 demonstrated FAZ changes were also related to medial temporal lobe atrophy (MTA) scores in individuals with early-onset dementia (EOD), whereas retinal microvasculature was correlated with white-matter hyperintensity [ 61 ]. Additionally, patients with AD and cognitive impairment have been found to have lower retinal capillary vessel density as well as flow density compared to controls [ 62 , 63 , 64 , 65 , 66 , 67 , 68 ] ( Figure 4 ).…”
Section: Ocular Biomarkers In Alzheimer’s Diseasementioning
confidence: 99%
“…In 2018, O’Bryhim et al noted that Aβ-positive preclinical patients had a greater foveal avascular zone (FAZ) on their OCTA in comparison to healthy people [ 60 ]. Subsequent studies by Zhang in 2022 demonstrated FAZ changes were also related to medial temporal lobe atrophy (MTA) scores in individuals with early-onset dementia (EOD), whereas retinal microvasculature was correlated with white-matter hyperintensity [ 61 ]. Additionally, patients with AD and cognitive impairment have been found to have lower retinal capillary vessel density as well as flow density compared to controls [ 62 , 63 , 64 , 65 , 66 , 67 , 68 ] ( Figure 4 ).…”
Section: Ocular Biomarkers In Alzheimer’s Diseasementioning
confidence: 99%